Structural and optical properties of electrodeposited Cu2O thin films. (2020) - Hssi, A. Ait; Atourki, L.; Labchir, N.; Abouabassi, K.; Ouafi, M.; Mouhib, H.; Ihlal, A.; Elfanaoui, A.; Benmokhtar, S.; Bouabid, K.
Abstract: In this work, we report on the synthesis of Cu2 O thin films by electrodeposition technique. The as-electrodeposited films at −0.5 V potential for 15 min in basic solution (pH = 9) are well crystallized in cubic structure, with 〈1 1 1〉 as preferential orientation and with lattice parameter a = 4.26 Å. The transmittance of Cu2 O films reveals that they have high optical transmission (>70%) with direct band gap energy in order of 2.23 eV. The density functional theory using the plane-wave-self-consistent field (PWSCF) was carried out for Cu2 O to determine some of their electronic properties. Theoretical analyses show that Cu2 O has a direct band gap with value 2.01 eV, which is consistent with the experimental results.